The Impact of Cruise Product Consumption Phases on Cruise Passenger Spending in a Non-Overnight Stay Port: Implications for Destination Managers - José-Pablo Abeal-Vázquez; Sarah Louise Moss; Andrea Teira-Fachado (Tourism and Hospitality)
The level of expenditure by cruise passengers in the various cities visited during their journey is a crucial variable for the key stakeholders involved in this industry. Promoting higher spending by cruise passengers in non-overnight stay ports is a challenge led by the destination manager. This study aims to shed light on the effect that different phases in the cruise passenger’s travel cycle have on their propensity to spend during their stay. Our case focuses on the city of A Coruña, a non-overnight stay port on Europe’s Atlantic arc routes, where the average spending per cruise passenger during their visit is quite low. The analysis considers the impact of passenger profiles and the cruise product consumption phases on the average spending per passenger. From a methodological perspective, we have applied logistic regression. The results indicate that the profile of the cruise passenger, variables related to the onboard journey, and the experience of the city are the factors with the greatest potential to increase cruise passenger spending during their visit to the city. This has allowed the areas of greatest impact and where actions should be focused to be identified for both the destination manager and key stakeholders.